PERAN PEMERINTAH DAERAH DALAM UPAYA MENINGKATKAN EKONOMI MELALUI PEMBERDAYAAN UMKM DI KOTA MATARAM - toyo, Tekla rensiana; Nazwin, Asfarony Hendra; Setiawan, Muh Rivandy (Institut Pemerintahan Dalam Negeri (IPDN), 2024)
MSMEs (Micro, Small, and Medium Enterprises) play a significant role in economic development in Mataram City, West Nusa Tenggara Province. Data shows that there are 22,473 micro, small, and medium enterprises operating in this area, reflecting the major contribution of MSMEs to local economic growth. This phenomenon has encouraged the Mataram City Government to develop various empowerment programs, including entrepreneurship training, providing capital through People's Business Credit (KUR), and facilitating product marketing. These efforts are in line with Law Number 20 of 2008 concerning MSMEs which emphasizes the importance of the role of MSMEs in encouraging equality and economic growth. This study aims to analyze the extent to which local government policies influence MSME empowerment in Mataram City. The research method used is a comprehensive literature study, supported by regional administrative data and previous scientific research results. This analysis focuses on the policy implementation process, the effectiveness of the programs implemented, and their direct impact on the local economy. The results of the study indicate that government initiatives in the fields of training, financing, and marketing have a positive impact on MSME growth. In particular, increasing entrepreneurial capacity and easy access to capital contribute to reducing unemployment rates and improving community welfare. In addition, MSME participation in marketing support programs has been proven to strengthen the competitiveness of local products in regional markets. Thus, targeted MSME empowerment programs are key to building a more inclusive and sustainable regional economy. These findings are expected to be a reference for stakeholders in formulating strategies and policies for local economic development in the future.